IMAGING DIAGNOSIS: FIBRODYSPLASIA OSSIFICANS PROGRESSIVA IN A CAT. Issue 5 (12th April 2013) - Klang, Andrea; Kneissl, Sibylle; Glänzel, Romana; Fuchs‐Baumgartinger, Andrea
Abstract : A 1‐year‐old female cat was presented for progressive alopecia, gait abnormalities, and stiffness. Radiography demonstrated multiple calcified lesions within the soft tissues of the cervical and thoracic spine, shoulder, and limbs. Postmortem computed tomography provided more detailed information on the distribution, pattern, and extension of lesions. In addition, computed tomography helped guide sample selection for histopathology. The final diagnosis was fibrodysplasia ossificans progressiva. This is a rare disorder of unknown etiology, characterized by fibrosis and heterotopic bone formation in connective tissues. To the authors' knowledge, this is the first report describing this disease in a European cat.